Morphometric and Bathymetric Characteristics and Trophic Status of Silosung Lake, Lintong Nihuta District, Humbang Hasundutan Regency, North Sumatra Province - Muhtadi, Ahmad; Silaban, Matthew Federich Willyam; Leidonald, Rusdi; Dewinta, Astrid Fauzia (Indonesian Journal of Agricultural Research, 2024)
Lakes can form naturally through natural events or artificially through human activities. Silosung Lake is a natural lake in Siponjot Village, Lintong Nihuta District, Humbang Hasundutan Regency. Lake morphometry refers to the physical characteristics of the lake body, while bathymetry refers to the measurement and mapping of the topographic conditions of the lake bottom. It is essential to know the morphometric and bathymetric characteristics and trophic status of the lake to achieve sustainable lake management. This study aims to determine the characteristics of bathymetry, morphometry, and tropic status of Lake Silosung. This research was conducted in July 2023. The data collection in this study includes lake perimeter data, lake depth data, lake length and width data, and lake water quality data. This research indicates that Silosung Lake has an area of 104,806.6 mÂ² with a lake perimeter length of 1,573.5 m, a maximum length of 474.53 m, and a maximum width of 420.62 m. The maximum depth is 17 m, the average depth is 10.09 m, the relative depth is 7.9% with an average slope of 15.9%, the compensation depth is 4.32 m, and the Shoreline Development Index (SDI) value is 2.74. The Morpho Edapic Index (MEI) value is 2.88. Silosung Lake has a lake water volume of 1,057,108.6 mÂ³. The average Tropic State Index (TSI) value is 15.71, indicating that the trophic status of Silosung Lake is oligotrophic, meaning its productivity is low.